TO THE PROBLEM OF IMPROVING THE QUALITY OF PREPARATION MODERN PRIMARY SCHOOL TEACHER (Pedagogy of Higher and Secondary Education, 2007)
The problem of increasing the quality of a modern primary school teacher training.